THEATRUM case: theatre as a model of cultural transformation - Evgeniy I. Gaponov (Управление культурой)
THEATRUM is a private theatre space from Verkhnyaya Pyshma, operating on the territory of one of the pavilions of the Museum Complex of Civil and Military Equipment, which is rightfully included in the list of the best museums in the world with thematic collections that have no analogues. The theatre is perceived as a new model of a cultural institution: flexible, creative, meaningful. The project has existed for three and a half years, but has already become an example of sustainable development in a complex environment. It does not just create events, but turns each of them into a message that can change the attitude towards the theatre, the city, history. In its playbill, performances, film projects, educational initiatives and technological solutions work not separately, but as a single system of meanings. In the interview with the director of the THEATRUM theatre, Evgeny Gaponov, we discussed what the model of development of the theatre venue is based on and how work with the audience is built into it.